The Role of Indocyanine Near-Infrared Fluorescence in Colorectal Surgery - Maione, Francesco; Manigrasso, Michele; Chini, Alessia; Vertaldi, Sara; Anoldo, Pietro; D’Amore, Anna; Marello, Alessandra; Sorrentino, Carmen; Cantore, Grazia; Maione, Rosa; Gennarelli, Nicola; D’Angelo, Salvatore; et al. (Frontiers in Surgery, 2022)
Purposes: The aim of this study was to evaluate the importance of Indocyanine Green on control of anastomosis perfusion and on anastomotic leakage rates during laparoscopic and robotic colorectal procedures. Methods: A retrospective review of patients underwent elective minimally invasive surgery for colorectal cancer since 1st January 2018 to 31st December 2020 was performed. All patients underwent Near Infrared Fluorescence-Indocyanine Green system in two moments: before performing the anastomosis and after completing the anastomotic procedure. Primary outcomes were the rate of intraoperative change in the surgical resection due to an inadequate vascularization and the rate of postoperative anastomotic leakage. Secondary outcomes were the postoperative complications, both medical than surgical (intra-abdominal bleeding, anastomotic leakage). Results: Our analysis included 93 patients. Visible fluorescence was detected in 100% of the cases. In 7 patients (7.5%) the planned site of resection was changed due to inadequate perfusion. The mean extension of the surgical resection in these 7 patients was 2.2±0.62. Anastomotic leakage occurred in 2 patients (2.1%). Other complications included 8 postoperative bleedings (8.6%) and 1 pulmonary thromboembolism. Conclusions: The intraoperative use of Near Infrared Fluorescence-Indocyanine Green in colorectal surgery is safe, feasible and associated with a substantial reduction in postoperative anastomotic leakage rate.